EFEKTIVITAS MODEL PEMBELAJARAN PjBL DENGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF SISWA MATERI SIKLUS AIR - Fajriyah Selomitha Putri Anam, Aisyah; Rosmiati; Ladyawati, Erlin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of elementary students’ reflective thinking ability in science learning, particularly in the topic of the water cycle. Teacher-centered instruction has limited students’ active participation, reduced meaningful connections between concepts and real-life phenomena, and minimized opportunities for reflective processes. This research aims to analyze the effectiveness of the Project Based Learning (PjBL) model integrated with a Deep Learning approach in improving fifth-grade students’ reflective thinking ability on the water cycle topic at SDN Dukuh Kupang II/489 Surabaya. The study employed a quantitative approach using a pretest–posttest experimental group design. The participants consisted of 56 students from classes V-A and V-B, both functioning as experimental groups. Research instruments included reflective thinking tests (pretest and posttest), learning implementation observation sheets, student response questionnaires, and reflective thinking attitude scales. Data were analyzed using descriptive analysis and N-Gain calculations to measure improvement levels. The findings indicate a significant improvement in students’ reflective thinking ability after the implementation of PjBL combined with the Deep Learning approach. Posttest scores were higher than pretest scores, with N-Gain results categorized as moderate to high in both classes. Students’ responses toward the learning process were positive, showing increased engagement, interest, and deeper conceptual understanding. Therefore, the integration of Project Based Learning and Deep Learning is effective in enhancing reflective thinking skills in elementary science education.